Democracy and Resurgence of Coup d’état in West Africa: Exploring the Role of Natural Resource Wealth - Odeh, Emmanuel Ejike; Odibo, Sunday Moses; Agbo, Henry C.; Onwo, Desmond (CV. Cendikiawan Muda Sriwijaya, 2025)
The study explores the link between natural resource wealth, democracy, and coup vulnerability in West Africa using the Resource Curse Theory. Despite its abundant resources, the region has experienced a resurgence of coups, posing threats to democratic gains and economic development. The study uses an ex-post facto research design and documentary data collection and content analysis to analyze the influence of natural resource wealth on democratic consolidation and coup vulnerability. The study posits that the abundance of resources has created a curse, fostering corruption, political instability, and military interference, increasing coup vulnerability. The study reveals that coups are more common in nations with weak democratic institutions, reliance on natural resources, and inadequate economic management. While democratic consolidation and economic diversification reduce coup risk, resource curse phenomena and weak democratic institutions increase susceptibility. To encourage sustainable development in West Africa and reduce coup risk, efficient management of natural resources, democratic consolidation, and economic diversity are needed. This study contributes to the discourse on the resource curse and the establishment of democracy.